Imaginaire national et laïcité. Penser l’identité avec le projet de Charte des valeurs - Sklaerenn Le Gallo (Communiquer)
The issue of cultural and religious diversity is important amongst Quebec’s public sphere. Indeed, there have been many initiatives conducted to reflect on the “management” of diversity in Quebec, in order to either supervise or limit it. In 2013, Bernard Drainville, minister for Democratic institutions, submitted his draft of the Charter of Quebec Values, naming it Because we believe in our values. The desire to frame the wearing of religious symbols in the public and political spheres in Quebec was apprehended with the objective of redefining the foundation of Québec’s identity. Our interest, here, lies in six personalities’ opinion, involved in the sovereignist movement, regarding this charter. We thus intend to investigate the possibility of there being disagreements and divergences amid the conception of a national model directed to define a particular québécois identity.